Information systems for top-level football with focus on performance analysis and healthy reference patterns - Blobel, T.; Lames, M. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
In football clubs there are different, traditionally isolated sources of information. This results in fundamental need for a central club information system (CIS). The conceptual development of such a system is the purpose of this research. The focus of this study is to combine data of the performance diagnostics and medical data for a model of healthy reference patterns. Therefore special standardised tests were developed and performed with a team of U17 (n=17) players from a German Bundesliga club. The aim is to make this data accessible for the employees of a football club by specific retrieval software.